An alternative colorimetric RT-LAMP assay for the rapid detection of SARS-CoV-2: development and validation in Thailand - Klayut, Wiphat; Wongchai, Thanee; Chuenchom, Nattagarn; Bhakdeenuan, Payu; Bunchoo, Supranee; Srisungngam, Sopa; Suphankong, Sirilada; Phetsuksiri, Benjawan; Uppapong, Ballang; Rudeeaneksin, Janisara (The Journal of Infection in Developing Countries, 2024)
Introduction: COVID-19, an emerging infectious disease caused by SARS-CoV-2, continues to be a global public health threat. The development of a colorimetric reverse transcription loop-mediated isothermal amplification (RT-LAMP) can extend the availability of simple, reliable molecular tests for the rapid detection of COVID-19. Methodology: The RT-LAMP assay was developed using a new primer set targeting a portion of SARS-CoV-2 orf8. The method was validated at 63 ºC for 60 minutes with naked-eye visualization of the color change. The clinical performance was compared to a real-time reverse transcription-polymerase chain reaction (rtRT-PCR) using 273 RNA samples extracted from nasopharyngeal swab specimens. Results: The developed RT-LAMP was specific to SARS-CoV-2 with a limit of detection at 15 RNA copies per reaction. The assay demonstrated diagnostic accuracy, sensitivity, specificity, positive predictive value, and negative predictive value of 90.48% (95% CI: 86.36–93.68%), 87.00% (95% CI: 81.53–91.33%), 100% (95% CI: 95.07–100%), 100% (95% CI: not available), and 73.74% (95% CI: 66.22–80.07%), respectively, compared to the rtRT-PCR. The greatest sensitivity of 98.03% (95% CI: 94.34–99.59%) was demonstrated in samples with the cycle threshold (Ct) values < 30 cycles. Conclusions: The RT-LAMP method in this study showed good performance. The assay can increase the scope of laboratory testing for rapidly detecting SARS-CoV-2 in Thailand. Due to a decrease in COVID-19 cases, its application is beneficial when commercial alternatives are unavailable.